Does macrolide use confer risk of out-of-hospital cardiac arrest compared with penicillin V? A Danish national case-crossover and case–time–control study - Lars Køber; Freddy Lippert; Charlotte Andersson; Peter E Weeke; Gunnar H Gislason; Frederik Boetius Hertz; Aksel Jensen; Jenny D Knudsen; Magnus Arpi; Christian Torp–Pedersen (BMJ Open)
Introduction and objectives Macrolides have been associated with proarrhythmic properties, but the evidence is conflicting. We evaluated the risk of out-of-hospital cardiac arrest (OHCA) associated with specific macrolides in a retrospective study. Associations between specific macrolides and OHCA were examined by conditional logistic regression analyses in case-crossover and case–time–control models, using penicillin-V treatment as the comparative reference. From nationwide registries, we identified all OHCAs in Denmark from 2001 to 2010 and use of antibiotics.Ethics The present study was approved by the Danish Data Protection Agency (Danish Data Protection Agency (ref.no. 2007-58-0015, local ref.no. GEH-2014-017, (I-Suite.nr. 02 735)).Participants We identified 29 111 patients with an OHCA. Of these, 514 were in macrolide treatment ≤7 days before OHCA and 1237 in penicillin-V treatment.Results In the case-crossover analyses, overall macrolide use was not associated with OHCA with penicillin V as negative comparative reference (OR=0.90; 95% CI 0.73 to 1.10). Compared with penicillin-V treatment, specific macrolides were not associated with increased risk of OHCA: roxithromycin (OR=0.97; 95% CI 0.74 to 1.26), erythromycin (OR=0.68; 95% CI 0.44 to 1.06), clarithromycin (OR=0.95; 95% CI 0.61 to 1.48) and azithromycin (OR=0.85; 95% CI 0.57 to 1.27).Similar results were obtained using case–time–control models: overall macrolide use (OR=0.81; 95% CI 0.62 to 1.06) and specific macrolides (roxithromycin (OR=0.70; 95% CI 0.49 to 1.00), erythromycin (OR=0.67; 95% CI 0.38 to 1.18), clarithromycin (OR=0.75; 95% CI 0.41 to 1.39) or azithromycin (OR=1.17; 95% CI 0.70 to 1.95)).Conclusion The risk of OHCA during treatment with macrolides was similar to that of penicillin V, suggesting no additional risk of OHCA associated with macrolides.